Temporary Lateral Tarsorrhaphy In Managing Corneal Ulceration Related To Facial Nerve Palsy : Case Report - Rosdiana, Eka; Samira, Cut Putri (Jurnal Ilmu Kedokteran dan Kesehatan, 2024)
Corneal ulceration is a breach in the corneal epithelial surface that can lead to blindness. Facial nerve palsy can lead to inadequate eyelid closure and reducing lubrication of the eye's surface. A 58-year-old man presented with a one-month history of worsening blurred vision, pain, and a whitish spot in the Right Eye (RE). He had been diagnosed with facial nerve palsy three months prior which hadn’t improved. Ophthalmic examination revealed reduced visual acuity, conjunctival hyperemia, hypopyon, and lagophthalmos with corneal exposure in RE. Fluorescent test showed 4x5 mm corneal ulceration with infiltrate. A neurological examination confirmed facial nerve involvement. After pharmacological treatment, a follow-up showed resolution of hypopyon but a persistent corneal ulcer with infiltrate. Long-term corneal exposure from lagophthalmos can cause corneal ulceration and thinning, especially in the lower part of cornea. This poses a therapeutic challenge. A temporary lateral tarsorrhaphy was performed to encourage healing of the corneal surface by optimizing eyelid positioning. One month post-procedure, the ulcer showed good re-epithelialization.